Gluability of Two Veneer Thickness Following Microwave Heat Gun Drying - wahyudi wahyudi (Masyarakat Peneliti Kayu Indonesia, 2008)
Faster drying, higher in drying rate and uniformity in moisture of dried veneer are key factors in assessing successful wood veneer drying. Microwave drying differs from conventional drying in the way that microwave energy causes excitation and friction (dissociation) of water molecules or water in wood, which manifest itself as heat. It is superior penetration and can enhance the rate of moisture evaporation. Heat gun is employed to absorb evaporated wood water from being humid. In contrast to microwave drying, conventional drying relies on heat conduction from outer surface wood layers towards the inner layers; so that the thicker the wood cross-section the slower the rate of evaporation. Successful wood drying are determined by faster drying, higher drying rate and uniformity in final moisture content. One of key factors in assessing further veneer drying is veneer gluability, which can be evaluated using percentage of wood failure and glueline shear strength. This research is aimed to investigate the effect of microwave heat gun drying on veneer gluability, using percentage of wood failures and glueline shear strength test as estimators. Three treatments were employed, plywood made of microwave heat gun, conventional and mixed dried-veneers, using ten replicates. The results indicated that no difficulties were found in gluing dried veneer, either pure microwave, conventional or mixed dried veneers. Surprisingly, it is also reported that microwave heat gun drying result in better veneer gluability.